Comprehensive Analysis of Innovations in Post-Surgical Pain Management and Patient Rehabilitation - Alsharif, Nasser Ali; Alsharif, Ahmad Alhassan; Alshareef, Khalid Hasan; Aldouh, Mohammad Douh; almansour, Hussain mana; Al Sharif, zayed Mohammed,; Alshareef, Yahya Alhassan Ali; Alshareef, Rabeiallah Nasser; Alsharif, Rakan Khaled Mohammed; AL-Zawaid, Hassan Mohsen Ali (Journal of Ecohumanism, 2024)
Post-surgical pain management and patient rehabilitation play crucial role in identifying factors explaining postoperative pain, thus reducing the risk of complications, prolonging the healing process, and enhancing the patient’s quality of life during rehabilitation. These are non-opioid analgesics, minimally invasive procedures, multimodal pain management, and digital health interventions because they enhance outcomes and diminish risks of opioid-based pain management where traditional methods were applied. The findings of contemporary research studies are integrated in this paper to focus on the effectiveness, the difficulties, and the opportunities of offered changes for the practices of clinical medicine.